Laporan Kasus : Pemeriksaan Forensik Pada Kasus Kecelakaan Lalu Lintas - Muhammad Sulfiqram Syam; Mauluddin Mauluddin; Denny Mathius; S. Zulfikar Assegaf (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2023)
Background: A traffic accident is an unexpected and unwanted road traffic event which is difficult to predict when and where it will occur, involving at least one vehicle with other road users or due to negligence in driving a vehicle, be it a car or motorcycle which can cause death, disability, serious injury or minor injury. Within the territory of Indonesia itself, every hour has an average of at least three people who die as a result of the accident with many causal factors such as the human factor itself, which is around 61%, then the vehicle factor is 9% and environmental factors and infrastructure contribute as much as 30%. Case Description : We report a case of a traffic accident with multiple trauma. This traffic accident involved 2 motorbike riders who were traveling at maximum speed so that they collided with a truck that was stopped at a red light in Makassar City, South Sulawesi, on Thursday 15 June 2022 at around 01.00 WITA and caused the two motorbike riders to die. The motorbike that was traveling at high speed suddenly stopped and hit the back of the truck, as a result the body moving at the speed of the vehicle suddenly experienced a deceleration, causing multiple trauma to several regions or organs of the body. The effects on the victim's corpse varied in the form of head injuries, open wounds, and fractures to several bones. Conclusion : Forensic examination is very useful to determine the cause of death, mechanism of death, and nature of death. In the medical report of a traffic accident, the forensic doctor can explain his findings in the form of a post mortem et repertum.